Cobalt Chloride Upregulates Impaired HIF-1α Expression to Restore Sevoflurane Post-conditioning-Dependent Myocardial Protection in Diabetic Rats - Wu, Jianjiang; Yang, Long; Xie, Peng; Yu, Jin; Yu, Tian; Wang, Haiying; Maimaitili, Yiliyaer; Wang, Jiang; Ma, Haiping; Yang, Yining; Zheng, Hong (Frontiers in Physiology, 2017)
Previous studies from our group have demonstrated that sevoflurane postconditioning (SPC) protects against myocardial ischemia reperfusion injury via elevating the intranuclear expression of hypoxia inducible factor-1 alpha (HIF-1α). However, diabetic SPC is associated with decreased myocardial protection and disruption of the HIF-1 signaling pathway. Previous studies have demonstrated that cobalt chloride (CoCl2) can upregulate HIF-1α expression under diabetic conditions, but whether myocardial protection by SPC can be restored afterward remains unclear. We established a rat model of type 2 diabetes and a Langendorff isolated heart model of ischemia-reperfusion injury. Prior to reperfusion, 2.4% sevoflurane was used as a post-conditioning treatment. The diabetic rats were treated with CoCl2 24 h before the experiment. At the end of reperfusion, tests were performed to assess myocardial function, infarct size, mitochondrial morphology, nitric oxide (NO), Mitochondrial reactive oxygen species (ROS), mitochondrial respiratory function and enzyme activity, HIF-1α, vascular endothelial growth factor (VEGF) and endothelial NO synthase (eNOS) protein levels. In addition, myocardial protection by SPC was monitored after the blood glucose levels were lowered by insulin. The diabetic state was associated with deficient SPC protection and decreased HIF-1α expression. After treating the diabetic rats with CoCl2, SPC significantly upregulated the expression of HIF-1α, VEGF and eNOS, which markedly improved cardiac function, NO, mitochondrial respiratory function, and enzyme activity and decreased the infarction areas and ROS. In addition, these effects were not influenced by blood glucose levels. This study proved that CoCl2 activates the HIF-1α signaling pathway, which restores SPC-dependent myocardial protection under diabetic conditions, and the protective effects of SPC were independent of blood glucose levels.